An analytical model for gas leakage through contact interface in proton exchange membrane fuel cells. (1st September 2022) - Qiu, Diankai; Liang, Peng; Zhao, Xiaojun; Wang, Yanbo; Peng, Linfa; Lai, Xinmin
Abstract: Sealing performance between two contacting surfaces is of significant importance to stable operation of proton exchange membrane (PEM) fuel cells. In this work, an analytical micro-scale approach is first established to predict the gas leakage in fuel cells. Gas pressure and uneven pressure distribution at the interface are also included in the model. At first, the micro tortuous leakage path at the interface is constructed by introducing contact modelling and fractal porous structure theory. In order to obtain the leakage at the entire surface, contact pressure distribution is predicted based on bonded elastic layer model. The gas leakage through the discontinuous interface can be obtained with consideration of convection and diffusion. Then, experiments are conducted to validate the numerical model, and good agreement is obtained between them. Finally, influences of surface topology, gasket compression and gasket width on leakage are studied based on the model. The results show that gas leakage would be greatly amplified when the asperity standard deviation of surface roughness exceeds 1.0 μm. Gaskets with larger width and smaller thickness are beneficial to sealing performance. The model is helpful to understand the gas leakage behavior at the interface and guide the gasket design of fuel cells. Graphical abstract: Image 1 Highlights: An analytical model is built to predict gas leakage rate in fuel cells. Uneven pressure distribution at the interface is considered in the model. Leakage is amplified when asperity height standard deviation exceeds 1.0 μm. Leakage becomes serious when gasket compression ratio is lower than 8%. Gaskets with larger width and smaller thickness are beneficial to sealing.